SCREENING OF NITRILE-DEGARADING ENDOPHYTIC BACTERIA FROM THE BIODIVERSITY OF INDONESIA - Atmosukarto, Ines I. C.; Sunarko, Bambang (Teknologi Indonesia, 2011)
Nitriles are an important group of compounds which appear in the environment via natural or industrial synthesis. Nitrile-metabolising microorganisms usually convert nitriles via one of the following two hydrolytic pathways: 1) conversion of the nitrile directly to its corresponding carboxylic acid and ammonia by nitrilase, and/or 2) conversion of the nitrile by nitrile hydratase to an intermediate amide, which is then converted by an amidase to the corresponding carboxylic acid and ammonia. The potential biotechnological application of these enzymes to produce amides and/or acids from nitriles has a major industrial interest. Higher plants are host to microorganisms, generally referred to as endophytic microbes (or endophytes) which colonise the internal tissue of living plants without causing overt negative effects to their host. Rare and biologically active compounds have been isolated from these microbes ranging from anti-infective activity, antioxidant, anticancer, insecticidal and others. Some of the compounds that have been discovered in endophytic microbes include taxol, cryptocin, cryptocandin, and ambuic acid amongst a few. However, the potential of this relatively untapped source of microbial diversity as a source of nitrile converting enzymes has yet to be evaluated. In this study we have tested approximately 850 bacterial endophytes for their ability to utilize acetonitrile (aliphatic nitrile) and benzonitrile (aromatic nitrile) as a sole source of energy, carbon and nitrogen for their growth. Based on their growth pattern, 97 isolates of those were able to utilize acetonitrile, of which 7 could also utilise benzonitrile. This result suggests that those isolates are likely to possess enzymes which are able to convert nitriles as indicated by the presence of metabolic byproducts such as carboxylic acid and ammonia. This is to our knowledge the first report of such activity for endophytic bacteria.